FREQUENCY OF METABOLIC SYNDROME IN TYPE-2 DIABETES MELLITUS - Kiani, Ismaa Ghazanfar; Khan, Adil Naseer; Yasir, Saadia; Baluch, Urooj Taheed (Journal of Ayub Medical College Abbottabad, 2016)
Background: Metabolic syndrome (MetS) is a cluster of coronary risk factors such as diabetes and pre-diabetes, abdominal obesity, high triglyceride (TG), low high density lipoprotein cholesterol (HDL-c) levels and high blood pressure (BP). It is estimated that around a quarter of the world's adult population have MetS and they are twice as likely to die from it and three times as likely to have a coronary event or stroke compared with people without the syndrome. Methods: This observational descriptive study was conducted at the Department of General Medicine, Federal Government Polyclinic Islamabad. All type-2 diabetics presenting in the outpatient and inpatient department during 11 months between the ages of 30-80 were enrolled. They were interviewed, blood pressure, waist circumference, fasting blood glucose, and lipid profiles were checked. Results: Of the 300 patients 165 (55%) were females and 135 (45%) were males with mean age 52.47±11.24 years. The mean duration of Diabetes Mellitus was 7.38±3.85 years. Metabolic Syndrome was present in 83% of the study population, 129 (43%) were male and 171 (57%) were female. The p-value was statistically significant on comparing the presence of the Metabolic Syndrome with waist circumference, serum triglyceride levels, and blood pressure as it was <0.05. The most commonly occurring finding was a decreased HDL-cholesterol in both genders. Conclusions: The MetS was present in 83% of the diabetic population, mostly in females with decreased HDL-cholesterol being the most common in both genders.